Wide White Space : Hinter dem Museum : 1966 1976. - De Decker, Anny; Coessens, Piet; Paleis voor Schone Kunsten Brussel; Kunstmuseum Bonn; Mac - Galeries Contemporaines des Musées de Marseille (Brussel : Paleis voor Schone Kunsten Brussel, 1995)
Andre, Carl ; Ammann, Jean-Christophe ; Appel, Karel ; Arakawa, Suhusaka ; Arman ; Artschwager, Richard ; Beuys, Joseph ; Beeren, Wim ; Becht, Frits ; Baumgarten, Lothar ; Baselitz, Georg ; Barry, Robert ; Broodthaers, Marcel ; Flavin, Dan ; Byars, James Lee ; Long, Richard ; etc.
Wide White Space : Hinter dem Museum : 1966 1976 / Behind the museum : 1966 1976, Paleis voor Schone Kunsten Brussel, 28.10. - 31.12.1994 / Kunstmuseum Bonn, 5.5. - 25.6.1995 / MAC, galeries contemporaines des Musées de Marseille, April - May 1996
boek
Keywords: Lohaus, Bernd